Innovative strategies in combating intervertebral disc degeneration: pathological mechanisms and biomaterial advancements - Ma, Long; Pan, Jizhou; Zhang, Jiankang; Liu, Fashun (Frontiers in Bioengineering and Biotechnology, 2025)
Intervertebral disc degeneration (IVDD) is a leading cause of chronic low back pain, significantly impacting the quality of life for millions of individuals worldwide. The onset of IVDD is associated with various factors such as age, lifestyle, and genetics, and its pathological mechanisms involve multidimensional interactions, including oxidative stress, inflammation, and extracellular matrix (ECM) metabolic disorders. During degeneration, there is a reduction in the number of nucleus pulposus cells (NPCs), resulting in an imbalance between the synthesis and degradation of the ECM, leading to changes in the disc’s morphology and biomechanical function, ultimately causing pain and mobility issues. As the global population ages, the incidence of IVDD continues to rise, necessitating the development of effective treatment strategies. Recent research into biomaterials, particularly hydrogels and stem cell technologies, has shown promise for disc regeneration, providing scaffolds to enhance cellular repair and facilitate drug delivery. This review comprehensively examines recent advancements in IVDD research, focusing on the pathological mechanisms and the potential application of biomaterials in treatment. Additionally, the integration of emerging technologies such as 3D printing and stem cell therapy represents a transformative approach in IVDD management. These findings open new avenues for targeted intervention strategies that address the underlying causes of IVDD, paving the way for improved clinical outcomes.